2012
DOI: 10.1007/s40333-013-0141-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of emitter discharge rates on soil salinity distribution and cotton (Gossypium hirsutum L.) yield under drip irrigation with plastic mulch in an arid region of Northwest China

Abstract: A field experiment was carried out to investigate the effects of different emitter discharge rates under drip irrigation on soil salinity distribution and cotton yield in an extreme arid region of Tarim River catchment in Northwest China. Four treatments of emitter discharge rates, i.e. 1.8, 2.2, 2.6 and 3.2 L/h, were designed under drip irrigation with plastic mulch in this paper. The salt distribution in the range of 70-cm horizontal distance and 100-cm vertical distance from the emitter was measured and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…The irrigation type [60], irrigation rate [46] and the irrigation amount [10] have effected on the cotton yield. Especially, Soil salinity and sodicity can be maintained at acceptable low levels by appropriate preplant irrigation [61].…”
Section: Water Use Efficiency In Different Saline Soilsmentioning
confidence: 99%
“…The irrigation type [60], irrigation rate [46] and the irrigation amount [10] have effected on the cotton yield. Especially, Soil salinity and sodicity can be maintained at acceptable low levels by appropriate preplant irrigation [61].…”
Section: Water Use Efficiency In Different Saline Soilsmentioning
confidence: 99%
“…Water shortage and soil salinization are the two critical problems affecting sustainability of the agriculture in arid regions (Chen et al 2010a;Danierhan et al 2013). Over 50 % of river water is developed for the purposes of irrigation in Xinjiang, north-west China, and more than 70 % of the developed rivers are inland (Li 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Treatments with and without plastic mulch have significant effects on soil water and salinity distribution (Selim et al 2013;Kirnak and Demirtas 2006). The wetting patterns of drip irrigation depend on several factors including the drip-line and dripper placement, soil texture, root-water uptake, irrigation intensity, and initial water content (Cook et al 2003;Kirnak and Demirtas 2006;Zumr et al 2006;Hao et al 2007;Shan et al 2011;Danierhan et al 2013;Wang et al 2014b). Bar-Yosef and Sheikholslami (1976) found that the soil water was prone to expanding in the vertical profile of sandy soil under drip irrigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plastic film mulching cultivation (PC) with drip irrigation has been promoted as a sound agricultural practice designed to improve the efficiency of use of soil nutrients by crops, and to improve the photosynthetic capacity and yield of crops (Danierhan et al, 2013;Dong et al, 2008;Liang et al, 2013). This type of cultivation is now widely applied in China (Li et al, 2004), including 1,000,000 ha in northwestern China in 2009 (Gu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%